Fixed point theorems for compatible mappings with applications to the solutions of functional equations arising in dynamic programmings - Nan-Jing Huang; Byung Soo Lee; Mee Kwang Kang (International Journal of Mathematics and Mathematical Sciences)
Some common fixed point theorems for compatible mappings are shown As an application, the existence and uniqueness of common solutions for a class of functional equations arising in dynamic programmings are discussed.